Math Bilbul “Alaihisalam” as a Learning Innovation During Covid 19: Math Bilbul “Alaihisalam” Sebagai Inovasi Pembelajaran Saat Pandemi Covid-19 - Robia Astuti; Nurmitasari, Nurmitasari; Sutriningsih, Naning (Halaqa: Islamic Education Journal, 2021)
This research is a research and development that aims to produce an interactive learning media product in the form of an educational game Math BilBul "alaihisalam" (Matematika Bilangan Bulat “ayo belajar operasi hitung secara islam”) that is feasible to use and integrates Islamic values and is effective in learning in the era pandemic covid-19. The research subjects were all fourth grade students for the 2020-2021 academic year in the odd semester of SD Muhammadiyah who were at the Sukoharjo Pringsewu branch level. The research method used is development research by adopting the steps of Thiagarajan commonly known as the 4-D development model, namely: Define, Design, Develop, and Disseminate. The data collection technique used is through instruments in the form of learning implementation observation sheets, validation sheets of learning media suitability with student analysis in online learning, student activity observation sheets in learning, student response questionnaires and learning outcomes tests. The results of this study are that an interactive learning media based on the Math BilBul “alaihisalam” educational game has been developed which is considered suitable for use based on the results of expert validation and is considered effective based on the implementation of learning which reaches 100%, student activity reaches 100%, student learning outcomes reach an average value. an average of 90, which is more than the KKM score, and a positive student response questionnaire that reaches 83.5%.